The Transmediality of Anachronism: Reconsidering the Revolutionary Representations of Antiquity and the Leftist Image of Qu Yuan. - Wang, Pu (Frontiers of Literary Studies in China, 2019)
"Make the past serve the present!" Thus goes Mao Zedong's slogan on how to appropriate the ancient in revolutionary times. In my previous studies, I have argued that the Chinese writers' engagement with the ancient gave rise to a platform of "necessary anachronism" in cultural transformation. This new project carries further this argument and draws attention to the transmediality in the leftist historical imagination. From the 1940s through the 1970s, the revolutionary representations of the ancient were simultaneously poetic, theatrical, intellectual, and cinematic, to say nothing about the calligraphic and visual adaptations they elicited. This current of reinventing the ancient manifested itself in the historical drama in wartime China and found a coda in the anti-colonial leftist cinematic adaptation of the historical play Qu Yuan in 1970s Hong Kong. Starting with a broader theoretical intervention into the issue of media, this paper emphasizes that the transmedial reinterpretation of the ancient in fact formed a mode of mediation between revolution and history, between politics and aesthetics. In the cultural regime of China's long revolution, the transference or translation of the allegorical-anachronistic energies among different media was a key site of signification, contestation, and crisis.